How return and risk experiences shape investor beliefs and preferences. (4th September 2015) - Hoffmann, Arvid O. I.; Post, Thomas
Abstract: Combining brokerage records and matching monthly survey measurements of a sample of individual investors from the Netherlands for the period April 2008 through March 2009, we examine how individual investors update their beliefs (return expectations and risk perceptions) and preferences (risk tolerance) as a result of their personal return and risk experiences. We find that investors' past returns positively impact return expectations and risk tolerance, and negatively impact risk perceptions. Realised risk, however, has no effect. That is, even in a highly volatile stock market period in which risk appears very salient, investors do not take it into account when updating their beliefs and preferences.